2009
DOI: 10.2340/16501977-0353
|View full text |Cite
|
Sign up to set email alerts
|

Phantom limb pain relief by contralateral myofascial injection with local anaesthetic in a placebo-controlled study: Preliminary results

Abstract: Contralateral injections of 1 ml 0.25% bupivacaine in myofascial hyperalgesic areas attenuated phantom limb pain and affected phantom limb sensation. The clinical importance of this treatment method requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This contact produced what the subject defined as a "queer feeling." 11 Moreover, somatosensory manipulation of painful muscle areas in the contralateral limb also seem to be able to modify PLRP, 22 further supporting the importance of any sensory inputs and indicating that even subtle changes in sensory information from both body sides can affect phantom limb awareness. Our…”
Section: Discussionmentioning
confidence: 94%
“…This contact produced what the subject defined as a "queer feeling." 11 Moreover, somatosensory manipulation of painful muscle areas in the contralateral limb also seem to be able to modify PLRP, 22 further supporting the importance of any sensory inputs and indicating that even subtle changes in sensory information from both body sides can affect phantom limb awareness. Our…”
Section: Discussionmentioning
confidence: 94%
“…Eleven trials including data from 324 participants assessed the effectiveness of local anaesthetics in providing pain relief after inguinal hernia repair, spinal surgery, amputation and breast cancer surgery. Risk of bias was evident in three studies, and concerned incomplete outcome data, random sequence generation and blinding, and early trial termination.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that local injection therapy may have effects beyond providing local peripheral blockade of pain input. One small observational study found that contralateral myofascial injection with local anesthetic in unilateral amputees attenuated PLP and PSs in the affected limb, though follow-up was limited to 1 hour 63. Whereas the precise mechanism for this effect is unclear, animal studies have demonstrated that blocking afferent inputs on the contralateral side can decrease spontaneous hyperactivity of wide dynamic response neurons on the injured side, suggesting that a spinal mechanism may be at work 64…”
Section: Treatmentmentioning
confidence: 99%